Place the headstones where they belong: Thomas Neibaur, WWI soldier - Fleek, Sherman L., author; Utah State University Press, publisher (Colorado State University. Libraries, 2008)
After a long journey from Sugar City, Idaho, to France's Argonne Forest France during World War I, young Thomas Neibaur found himself in the core of the American Expeditionary Force's most important offensive. After becoming separated in advance of his unit, he, despite serious wounds, single-handedly stopped a German counterattack at a critical hill known as Côte de Châtillon. For this remarkable feat of valor, he received the Medal of Honor and other awards, becoming the first Idaho and first Mormon recipient of the nation's highest combat award. But after a heroic return and brief celebrity, his life followed a tragic downward arc, culminating in his attempt to return his medal because, as he put it, it could not feed his family.
Keywords: World War, 1914-1918 -- Campaigns -- France; Medal of Honor -- Biography; Mormons -- Idaho -- Biography; Soldiers -- United States -- Biography; Medal of Honor; Mormons -- Idaho; Soldiers -- United States; History; United States; United States -- Medals, badges, decorations, etc.; Neibaur, Thomas Croft, 1898-1942; United States. Army. Infantry Regiment, 167th; United States. Army -- Medals, badges, decorations, etc.; United States. Army -- Biography